The Effects of Irradiance on Translucency and Surface Gloss of Different Bulk-Fill Composite Resins: An in vitro Study - Bin Nooh AN; Al Nahedh H; AlRefeai M; AlKhudhairy F (Dove Medical Press, 2020)
Abrar N Bin Nooh, Hend Al Nahedh, Mohammad AlRefeai, Fahad AlKhudhairy Restorative Dental Sciences Department, College of Dentistry, King Saud University, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Abrar N Bin NoohRestorative Dental Sciences Department, College of Dentistry, King Saud University, PO Box 60169, Riyadh 11545, Kingdom of Saudi ArabiaTel +966 506420828Email Abrar.nasser@hotmail.comPurpose: The influence of different light-emitting diode (LED) curing light intensities on the translucency and surface gloss of bulk-fill resin-based composite (RBC) restorative materials was evaluated.Materials and Methods: Forty specimens of each RBC (Filtek One bulk-fill posterior, Reveal HD bulk, Tetric N-Ceram, and Filtek Z350) were prepared. The RBCs were shaped into molds and cured using an LED curing light unit at high intensity (1,200 mW/cm2) for 20 s and low intensity (650 mW/cm2) for 40 s. A spectrophotometer was used to determine the translucency, and a gloss meter was used to evaluate surface gloss. Data were analyzed using one- and two-way analysis of variance (ANOVA), independent t-test, and Tukey’s and Scheffe’s post hoc multiple comparison tests.Results: The highest translucency value was observed for Reveal HD (7.688 ± 0.861) with a high curing intensity, while Filtek One showed the lowest value (1.750 ± 0.376) with a low curing intensity. The materials showed no significant difference in surface gloss with a high curing intensity. With low-intensity light curing, Filtek One showed the highest gloss value (55.270 ± 10.106), while Tetric N-Ceram and Reveal HD showed the lowest gloss values (35.560 ± 6.533 and 35.680 ± 6.648, respectively).Conclusion: Curing light intensity had no effect on both the gloss and translucency for all the materials tested, although for Tetric N-Ceram, higher intensity corresponded to higher gloss values while for Filtek One, higher intensity corresponded to a higher translucency value.Keywords: curing light intensity, bulk-fill resin-based composites, translucency, surface gloss